Hubungan antara Tingkat Penalaran Formal dan Tingkat Perkembangan Konsep Geometri Siswa - Sunardi Sunardi (Universitas Negeri Malang, 2016)
This study examined the level of students' logical thinking ability and the level of students' understanding in geometry, and also the relationship between the students' level of logical thinking and students' level of understanding in geometry. The tests of logical thinking and geometry concept development level were administered to 387 students of the third year science classes selected from 10 State Senior High Schools in Jember, East Java. The results indicated that 8.01%, 24.81%, 29.97%, 37.21% students were respectively at concrete, transition, early formal, and formal levels; and 14.47%, 31.52%, 40.05%, 13.44%, 0.52%, 0% were at previsualization, visualization, analysis, informal deduction, deduction, and rigor respectively. There was a significant relationship between students' level of logical thinking ability and their level of understanding in geometry